Healthcare choices following mild traumatic brain injury in Australia - Jacinta Thorne; Shaun Markovic; HuiJun Chih; Elizabeth Thomas; Amanda Jefferson; Samar Aoun; Melinda Fitzgerald; Sarah Hellewell (BMC, 2022)
Abstract Background Accurate data on the types of healthcare people seek in the early stages following mild traumatic brain injury (mTBI) in Australia is lacking. We sought to investigate the types of healthcare people seek following mTBI, including seeking no care at all; ascertain the demographic, pre- and peri-injury factors, and symptom characteristics associated with the care that people access; and examine whether choice of care is associated with symptomatic recovery and quality of life. Methods An online retrospective survey of Australians aged 18 to 65 years who had experienced a self-reported 'concussion' (mTBI) within the previous 18 months. Types of healthcare accessed were investigated, as well as those who did not seek any care. Data were analysed using frequency and percentages, chi-squared tests and logistic regression models. Results A total of 201 respondents had experienced a self-reported 'concussion' but 21.4% of the respondents did not seek any care. Of the 183 respondents who sought healthcare, 52.5% attended a hospital Emergency Department, 41.0% attended a general practitioner and 6.6% accessed sports-based care. Compared to their counterparts, those who had a lower level of education (p = 0.001), had experienced previous mTBI (p = 0.045) or previous mental health issues (p = 0.009) were less likely to seek healthcare, whilst those who had experienced loss of consciousness (p = 0.014), anterograde (p = 0.044) or retrograde (p = 0.009) amnesia, and symptoms including drowsiness (p = 0.005), nausea (p = 0.040), and feeling slow (p = 0.031) were more likely to seek care. Those who did not seek care were more likely to recover within one month (AOR 4.90, 95%CI 1.51 - 15.89, p = 0.008), albeit the relatively large 95%CI warrants careful interpretation. Compared to seeking care, not seeking care was not found to be significantly associated with symptom resolution nor quality of life (p > 0.05). Conclusions This study provides unique insight into factors associated with healthcare utilisation in the early stages following mTBI, as well as outcomes associated with choice of care, including not seeking care. Delivering targeted community education on the signs and symptoms of mTBI, and the advantages of seeking care following injury is an important step forward in the management of this challenging condition.